1999
DOI: 10.1139/f98-175
|View full text |Cite
|
Sign up to set email alerts
|

Larval fishes of a Middle Atlantic Bight estuary: assemblage structure and temporal stability

Abstract: We collected weekly, quantitative ichthyoplankton samples over 6 years (1989-1994, 1309 samples) to identify temporal scales of variability in the abundance and occurrence of larval fish assemblages near Little Egg Inlet in southern New Jersey, U.S.A. We collected species that spawn in the estuary (30%), both the estuary and continental shelf (35%), continental shelf (25%), and the Sargasso Sea (10%). The following analyses suggest an annually repeated seasonal progression of species assemblages: (i) the rank … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
36
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 24 publications
11
36
1
Order By: Relevance
“…Portions of the flood tide waters from the ocean are diverted into the mouth of Little Sheepshead Creek (Charlesworth 1968;Chant et al 2000). Recent work has shown that ichthyoplankton samples collected from a bridge at this location are representative of the larger estuary (Witting et al 1999;Chant et al 2000;Neuman et al 2002).…”
Section: Sampling Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Portions of the flood tide waters from the ocean are diverted into the mouth of Little Sheepshead Creek (Charlesworth 1968;Chant et al 2000). Recent work has shown that ichthyoplankton samples collected from a bridge at this location are representative of the larger estuary (Witting et al 1999;Chant et al 2000;Neuman et al 2002).…”
Section: Sampling Sitesmentioning
confidence: 99%
“…1), leptocephali entering the estuary were collected with, three 30 min sets of a plankton net. Additional details of this sampling program are available (Witting et al 1999;Able and Fahay 2010). At Beaufort Inlet, leptocephali were collected with a plankton net which was deployed during night-time flood tides and sampled the surface (0-1 m) (Fig.…”
Section: Sampling For Leptocephalimentioning
confidence: 99%
“…Atlantic Ocean water flows into the estuary through Little Egg Inlet during flood tides, with portions diverted into the mouth of Little Sheepshead Creek Charlesworth 1968). Previous work has shown that ichthyoplankton samples collected from Little Sheepshead Creek are representative of the estuarine assemblage Neuman et al 2002;Witting et al 1999).…”
Section: Study Areamentioning
confidence: 97%
“…Sampling of larvae and pelagic juvenile fish in the Great Bay-Little Egg Harbor estuary has occurred on a weekly basis year-round since 1989 (Able and Fahay 2010;Witting et al 1999). A 1-m diameter, circular plankton net (1 mm mesh) fitted with a General Oceanics flowmeter is suspended from a bridge over Little Sheepsheads Creek to a depth of 1.5 m during night-time flood tides in these well-mixed waters (Table 1; Fig.…”
Section: Field Samplingmentioning
confidence: 99%
See 1 more Smart Citation